Identifying Generational Cohorts in Sarawak - Tinga, Hiram; Ernest Cyril, de Run; Fam, Kim-Shyan (Universiti Malaysia Sarawak, 2012)
The purpose of this paper is to deliberate on efforts to utilize the theories of generations to identify generational cohorts in Sarawak. A qualitative study was carried out via in-depth interview using a purposive sampling method to determine major societal events in the state. Interviews were recorded, transcribed, and analyzed using content analysis. Descriptive analysis was used to assess the frequency of the recalled events and their distribution by age range. Accordingly five generational cohorts were identified, and labeled as neoteric-inheritors, prospective-pursuers, social-strivers, idealistic-strugglers and battling-lifers. The results show that the people in the same cohorts recall the same events that occurred during their formative years and supports past studies that personal attachment to events in the coming-of-age times is a major determinant of a cohort. This validates past findings and lays the groundwork for further analyses on cohort characteristics and use. Recommendations for management are provided.